Miniature all-optical-fiber pH sensor based on rare earth ion doped nanocrystalline and preparation method and application of miniature all-optical-fiber pH sensor
By loading rare earth ion-doped nanoparticles on the surface of glass fiber microsphere cavity and collecting fluorescence signals through the optical fiber optical path, the problem of difficult to achieve manipulated fluorescence collection and transmission at high spatial resolution is solved, and efficient and accurate pH monitoring is achieved.
Patent Information
- Application Number
- CN202411790665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
AI Technical Summary
Rare-earth ion-doped nanocrystals are difficult to achieve manipulated fluorescence collection and transmission at high spatial resolution, making it difficult to achieve accurate pH positioning monitoring.
The fluorescence response detection of rare-earth ion-doped nanoparticles is achieved by loading rare-earth ion-doped nanoparticles on the surface of the glass fiber microsphere cavity, and providing excitation light through the fiber optical path.
A full-fiber micro pH sensor with high spatial resolution, flexible manipulation, stability and accuracy can maintain stable luminescence in a strong acid or strong alkali environment, improving the accuracy of monitoring results.
Smart Images

Figure CN119643521A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical devices, and in particular relates to a miniature all-optical fiber pH sensor based on rare earth ion-doped nanocrystals, and a preparation method and application thereof. Background Art
[0002] Accurate monitoring of pH (pondus Hydrogenii, acidity and alkalinity) values plays a vital role in many fields, including industrial production, water quality monitoring, ecological protection, sewage treatment, and human health. With the popularization of pH sensors in various fields, higher requirements are placed on the portability and spatial resolution of pH sensors.
[0003] The fluorescence emission of rare earth ions is very sensitive to the pH value of the environment. The use of the change in the fluorescence intensity ratio of rare earth ions with the pH value to detect pH value can achieve portability and effectively improve the spatial resolution of detection. However, the nanoscale size makes it difficult to collect and transmit the fluorescence detection of rare earth ion-doped nanocrystals at high spatial resolution. At the same time, the uncontrollability of nanocrystals makes it difficult to achieve accurate positioning monitoring.
[0004] Therefore, high spatial resolution detection of pH value by rare earth ion-doped nanocrystals has important significance and application prospects. How to achieve controllable fluorescence collection and transmission of rare earth ion-doped nanocrystals at high spatial resolution has become an urgent problem to be solved. Summary of the invention
[0005] In view of the above technical status and existing deficiencies, the purpose of the present invention is to provide a miniature all-fiber pH sensor based on rare earth ion doped nanocrystals and its preparation method and application. The preparation method of the present invention is simple in process and can obtain an all-fiber micro pH sensor with high spatial resolution, flexible controllability, high stability, repeatability and accuracy.
[0006] The purpose of the present invention can be achieved through the following technical solutions.
[0007] A miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals comprises rare earth ion-doped nanoparticles, a glass fiber microsphere cavity and an optical fiber optical path. The rare earth ion-doped nanoparticles are loaded on the surface of the glass fiber microsphere cavity. The glass fiber microsphere cavity and the optical fiber optical path are interconnected to form an optical path. The rare earth ion-doped nanoparticles are rare earth ion-doped nanocrystals or nanoparticles of a matrix wrapped around rare earth ion-doped nanocrystals. The rare earth ion-doped nanocrystals have a light response to pH. The optical fiber optical path provides excitation light and collects emission light.
[0008] Preferably, the rare earth ion-doped nanocrystal comprises rare earth ions and a matrix;
[0009] More preferably, the rare earth ion is selected from Er 3+ 、Tm 3+ At least one of;
[0010] Further preferably, the molar doping amount of rare earth ions is 1 to 3%;
[0011] Further preferably, the matrix is a rare earth fluoride;
[0012] More preferably, the matrix is selected from a mixture of one or more of NaYF4, NaGdF4, NaLuF4, NaScF4, NaYbF4 and LiYF4;
[0013] Further preferably, the rare earth ion-doped nanocrystals further include Yb 3+ Co-doping.
[0014] More preferably, Yb 3+ The molar doping amount is 10 to 40%;
[0015] Preferably, the structure of the rare earth ion-doped nanocrystal is a nanocrystal homogeneously doped with rare earth ions, and the structure of the nanoparticles of the matrix wrapped around the rare earth ion-doped nanocrystal is a core-shell structure formed by wrapping a layer of undoped matrix around the nanocrystal homogeneously doped with rare earth ions;
[0016] Preferably, the size of the rare earth ion-doped nanoparticles is less than or equal to 100 nm.
[0017] Preferably, the diameter of the glass fiber microsphere cavity is 8 μm to 300 μm;
[0018] Preferably, the rare earth ion-doped nanoparticles are loaded onto the surface of the glass optical fiber microsphere cavity and then subjected to heat treatment.
[0019] Preferably, the optical fiber optical path is connected to the excitation source and the spectrometer via a fiber optic beam splitter.
[0020] Further preferably, one end of the beam splitting end of the optical fiber beam splitter is connected to the corresponding excitation source, and the other end is connected to the spectrometer.
[0021] The method for preparing the above-mentioned micro all-optical fiber pH sensor based on rare earth ion doped nanocrystals comprises the following steps:
[0022] (1) dispersing rare earth ion-doped nanoparticles in a non-polar organic solvent to obtain a dispersion;
[0023] (2) immersing the glass fiber microsphere cavity in the dispersion liquid and allowing it to stand (under the action of van der Waals force, the rare earth ion-doped nanoparticles are uniformly coated on the surface of the glass fiber microsphere cavity), taking it out for heat treatment, and cooling it to obtain a glass fiber microsphere cavity loaded with rare earth ion-doped nanoparticles (the rare earth ion-doped nanoparticles slightly melt at high temperature and adhere more firmly to the surface of the glass fiber microsphere cavity after cooling);
[0024] (3) Connecting the glass fiber microsphere cavity loaded with rare earth ion-doped nanoparticles to the optical fiber optical path to obtain a miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals.
[0025] Preferably, in step (1), the rare earth ion-doped nanoparticles are prepared by a wet chemical method;
[0026] Preferably, in step (1), the non-polar organic solvent is cyclohexane;
[0027] Preferably, in step (1), the concentration of the rare earth ion-doped nanoparticles in the dispersion is 0.005 mol / L to 0.1 mol / L, calculated as rare earth ion-doped nanocrystals (for homogeneously doped nanocrystals, the concentration is calculated as total rare earth elements; for core-shell structured nanoparticles, the concentration is calculated as total rare earth elements in the core).
[0028] Preferably, in step (2), the standing time is 10s to 5min;
[0029] Preferably, in step (2), the heat treatment temperature is 250 to 300° C., and the heat treatment time is 2 to 5 hours;
[0030] Preferably, in step (2), the preparation method of the glass optical fiber microsphere cavity is as follows:
[0031] The glass optical fiber is heated, and the glass optical fiber is drawn into a tapered optical fiber by a melt drawing method, and is cut from the thinnest part to obtain a single-taper glass optical fiber. The tapered end of the single-taper glass optical fiber is heated and melted, and under the action of surface tension, the melted tapered end automatically forms a micro-spherical cavity;
[0032] Further preferably, the glass optical fiber is a (commercial) quartz optical fiber.
[0033] Further preferably, the heating source is an oxyhydrogen flame or a carbon dioxide laser.
[0034] Preferably, in step (3), the cavity of the glass fiber microsphere loaded with rare earth ion-doped nanoparticles is connected to the optical fiber optical path by fusion-connecting the optical fiber end of the glass fiber microsphere to the optical fiber of the optical fiber optical path.
[0035] Preferably, in step (3), the optical fiber optical path uses the same commercial quartz optical fiber as the glass fiber microsphere cavity.
[0036] The above-mentioned miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals is used for monitoring pH value.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] (1) The present invention effectively improves the spatial resolution of pH detection technology, which can reach up to several microns, fundamentally breaking the limitation of spatial size on pH detection technology, and the higher spatial resolution can realize accurate fixed-point pH monitoring.
[0039] (2) The present invention uses a simple heat treatment method to firmly coat the rare earth ion-doped nanoparticles on the surface of the microsphere cavity, so that the entire sensor can maintain stable luminescence in strong acid and strong alkaline environments, thereby allowing the nanoparticles to directly contact the test environment, which is beneficial to improving the accuracy of the monitoring results.
[0040] (3) The present invention uses commercial quartz optical fiber to simultaneously transmit excitation light and emission light, and excites the nanoparticles coated on the surface of the microsphere through total reflection of light in the microsphere cavity while collecting its fluorescence signal, thereby achieving full optical fiberization. Therefore, the pH sensor described in the present invention has extremely high controllability and portability, and can monitor pH in a variety of complex structures, such as the confined space and curved tubular structure shown in Example 1. In addition, the control accuracy is further improved, and the pH sensor described in the present invention can be used to draw a multi-dimensional pH value distribution map.
[0041] (4) The present invention uses fluorescence intensity ratio to monitor pH value. This technology does not require a reference element and is less affected by the external environment. It can work in some strong electric field or strong magnetic field environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of the device structure of a miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals obtained in an embodiment of the present invention.
[0043] Figure 2 The NaYF4:20% Yb obtained in Example 1 of the present invention 3+ ,2%Er 3+ @Scanning electron microscope image of NaYF4 nanoparticle-coated quartz fiber microsphere cavity after heat treatment.
[0044] Figure 3 The NaYF4:20%Yb 3+ ,2%Er 3+ @Spectral graph of the miniature all-fiber pH sensor based on NaYF4 nanoparticles in different pH environments.
[0045] Figure 4 The NaYF4:20%Yb 3+ ,2%Er 3+ @The intensity ratio of green light to red light of the micro all-fiber pH sensor based on NaYF4 nanoparticles at different pH values and the corresponding fitting curve.
[0046] Figure 5 The NaYF4:20% Yb obtained in Example 1 of the present invention 3+ ,2%Er 3+ @The spectra of NaYF4 nanoparticle-coated glass fiber microsphere cavity immersed in strong acid (pH value between 1 and 2) for different time periods without heat treatment.
[0047] Figure 6 The NaYF4:20%Yb 3+ ,2%Er 3+ @The emission intensity of the micro all-fiber pH sensor based on NaYF4 nanoparticles changes over time in a strongly acidic environment (pH value between 1 and 2).
[0048] Figure 7 The NaYF4:20%Yb 3+ ,2%Er 3+ @The emission intensity of the micro all-fiber pH sensor based on NaYF4 nanoparticles changes over time in a strongly alkaline environment (pH value between 13 and 14).
[0049] Figure 8 The NaYF4:20%Yb 3+ ,2%Er 3+ @Photo and spectrum of the miniature all-fiber pH sensor based on NaYF4 nanoparticles working in a confined space.
[0050] Fig. 9 The NaYF4:20%Yb 3+ ,2%Er 3+ @Photo of the working of the micro all-fiber pH sensor based on NaYF4 nanoparticles in an S-shaped capillary.
[0051] Fig.10 The NaYF4:1%Er obtained in Example 2 of the present invention 3+ Optical fluorescence photograph and spectrum of nanocrystal micro-all-fiber pH sensor.
[0052] Fig.11 The NaYF4:40%Yb 3+ ,1%Tm3+ Optical fluorescence photograph and spectrum of the miniature all-fiber pH sensor based on @NaYF4 nanoparticles.
[0053] Fig.12 The NaGdF4:20%Yb 3+ ,2%Er 3+ Spectral graph of nanocrystal-based miniature all-fiber pH sensor. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below with reference to examples and drawings, but the embodiments of the present invention are not limited thereto.
[0055] Example 1
[0056] Based on NaYF4:20%Yb 3+ ,2%Er 3+ The invention discloses a micro all-fiber pH sensor of NaYF4 nanoparticles and a preparation method thereof, comprising the following steps:
[0057] (1)NaYF4:20%Yb 3+ ,2%Er 3+ @ Preparation of NaYF4 nanoparticles:
[0058] Add 3mL of oleic acid and 7mL of 1-octadecene to a 50mL two-necked flask, add 2mL of 0.2mol / L Ln(CH3CO2)3 (Ln=Y, Yb and Er) solution according to the established stoichiometric ratio (Y:Yb:Er=78:20:2), stir magnetically at 150℃ for 1h, and cool to room temperature. Then dissolve 1mmol of NaOH and 1.6mmol of NH4F in 5mL of methanol solution, add to the above mixed solution, stir magnetically at 50℃ for 0.5h, then heat to 100℃ and stir for 1h. Finally, evacuate, introduce inert atmosphere, heat the mixed solution to 290℃, and stir magnetically at 1.5h. After the reaction is completed, cool to room temperature, centrifuge with alcohol, and use the purified NaYF4:20%Yb 3+ ,2%Er 3+ The nanocrystals were dispersed in 4 mL of cyclohexane (the particle size of the nanocrystals was ∼32 nm, and the concentration of the nanocrystal dispersion was 0.1 mol / L).
[0059] The NaYF4:20%Yb 3+ ,2%Er 3+ Nanocrystals were used as crystal nuclei, and a layer of NaYF4 was grown on their surface using a similar method to prepare NaYF4:20% Yb 3+ ,2%Er 3+@NaYF4 core-shell structure nanoparticles. Add 3mL oleic acid, 7mL 1-octadecene and 2mL 0.2mol / L Y(CH3CO2)3 solution into a 50mL two-necked flask. Stir the mixed solution at 150℃ for 1h and cool to room temperature. Then add 4mL NaYF4:20%Yb obtained in the previous step. 3+ ,2%Er 3+ Then, 1 mmol of NaOH and 1.6 mmol of NH4F were dissolved in 5 mL of methanol solution and added to the above mixed solution. The mixture was stirred at 50 °C for 0.5 h and then heated to 100 °C for 1 h. Finally, the mixture was vacuumed and inert atmosphere was introduced. The mixed solution was heated to 290 °C and stirred at a constant speed for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature and purified by centrifugation with alcohol. The purified NaYF4:20%Yb 3+ ,2%Er 3+ @NaYF4 nanoparticles were dispersed in 4 mL of cyclohexane (the particle size of the nanoparticles was ~45 nm, and the concentration of the nanoparticle dispersion was 0.1 mol / L in terms of nanocrystals).
[0060] (2) Preparation of glass fiber microsphere cavity: Strip a small section of the coating of commercial quartz optical fiber, clamp one end of the optical fiber with a vertical clamp, hang a weight on the other end, heat the middle of the stripped coating optical fiber with hydrogen-oxygen flame or CO2 laser, and use the gravity of the weight to pull the optical fiber into a micro / nano-scale tapered optical fiber. Then cut the tapered optical fiber from the middle, focus the hydrogen-oxygen flame or CO2 laser on the tail end of the single-taper optical fiber, melt the end, and automatically form a microsphere cavity (diameter 50μm) under the action of surface tension.
[0061] (3) Immerse the glass fiber microsphere cavity obtained in step (2) into the NaYF4:20% Yb 3+ ,2%Er 3+ @NaYF4 nanoparticles were placed in a cyclohexane dispersion for 30 seconds. Through van der Waals interaction, NaYF4:20% Yb 3+ ,2%Er 3+ @NaYF4 nanoparticles are uniformly coated on the surface of the microsphere cavity.
[0062] (4) The optical fiber microsphere cavity coated with nanoparticles was placed in a muffle furnace, and the temperature was increased to 250°C at a heating rate of 5°C / min, and then kept at this temperature for 3 hours. After the end of the heat preservation, it was cooled to room temperature in the furnace.
[0063] (5) Using a fiber fusion splicer, the heat-treated tail fiber of the microsphere cavity is fused with the beam combining end of the fiber beam splitter. One end of the beam splitter is fused with a 980nm fiber laser, and the other end is connected to a fiber spectrometer. When connecting, a filter is placed between the fiber and the spectrometer to obtain a NaYF4:20% Yb 3+ ,2%Er 3+ @NaYF4 nanoparticles based miniature all-fiber pH sensor.
[0064] The schematic diagram of the device structure of the miniature all-fiber pH sensor obtained in this embodiment is shown in Figure 1 As shown, it is composed of a glass fiber microsphere cavity coated with rare earth doped nanocrystals, an optical fiber optical path, an optical fiber beam splitter, a pump source, a filter, and a spectrometer. In this example, a 980nm optical fiber laser enters the microsphere cavity through total reflection in the optical fiber optical path, and excites the nanocrystals coated on the surface of the microsphere cavity through total reflection in the microsphere cavity. After being excited, the emission light of the nanocrystal enters the microsphere cavity, returns to the optical fiber optical path through total reflection, is split by the optical fiber beam splitter, and is captured by the spectrometer. The filter can remove most of the excitation source signals, and the corresponding pH value can be obtained by analyzing the captured fluorescence signal.
[0065] The NaYF4:20%Yb obtained after heat treatment in this example 3+ ,2%Er 3+ @Scanning electron microscope image of NaYF4 nanoparticles coated quartz fiber microsphere cavity Figure 2 As shown in the scanning electron microscope image, it can be seen that after heat treatment, the fluorescent nanoparticles are still evenly coated on the surface of the microsphere cavity, which can reduce the impact on the quality factor of the microsphere.
[0066] The spectra of the miniature all-fiber pH sensor obtained in this example in solutions with different pH values are shown in the figure below: Figure 3 As shown in the figure, it can be seen that in different pH solutions, Er 3+ The emission will show obvious changes, such as the fluorescence intensity ratio of green light to red light, and the fluorescence intensity ratio of green light to blue light. Figure 4 As shown in the figure, in acidic conditions, the intensity ratio of green light at 540nm and red light at 661nm decreases with the increase of pH value, and through fitting, a good linear relationship is shown between the two; while in alkaline conditions, the intensity ratio of green light at 540nm and red light at 661nm increases with the increase of pH value, and through fitting, a good exponential relationship is shown between the two. Using this law, the miniature all-fiber pH sensor obtained in this embodiment can measure pH value. The glass fiber microsphere cavity coated with nanoparticles that have not been heat-treated in this embodiment is placed in a strong acid solution (pH value between 1 and 2), as shown in the figure. Figure 5 As shown in Figure 2, the emission intensity decreases rapidly, and after heat treatment, Figure 6 As shown in , its emission intensity can maintain a stable output in the same strong acid solution. At the same time, in a strong alkaline solution (pH value between 13 and 14), its emission intensity can also maintain a stable output after heat treatment, as shown in Figure 7 As shown, the miniature all-fiber pH sensor in this embodiment has good stability when monitoring pH value. Based on the protection of the organic coating layer, the quartz optical fiber has good flexibility. Therefore, the miniature all-fiber pH sensor in this embodiment has good controllability, as shown Figure 8 As shown, real-time pH monitoring can be performed in a confined space. The spatial resolution of the prepared microsphere cavity can reach the micrometer level, and the detection signal is transmitted through optical fiber. Therefore, the micro all-optical pH sensor in this embodiment can be used for pH sensing in some complex structures. For example, the pH value at a precise position can be obtained in a curved capillary pipette, such as Fig. 9 shown.
[0067] Example 2
[0068] Based on NaYF4:1%Er 3+ A nanocrystalline micro all-optical pH sensor and a preparation method thereof, comprising the following steps:
[0069] (1)NaYF4:1%Er 3+ Preparation of nanocrystals: Add 3mL of oleic acid and 7mL of 1-octadecene to a 50mL two-necked flask, add 2mL of 0.2mol / L Ln(CH3CO2)3 (Ln=Y, Er) solution according to the established stoichiometric ratio (Y:Er=99:1), stir magnetically at a constant speed for 1h at 150℃, and cool to room temperature. Then dissolve 1mmol of NaOH and 1.6mmol of NH4F in 5mL of methanol solution, add to the above mixed solution, stir magnetically at a constant speed for 0.5h at 50℃, then heat to 100℃ and stir for 1h. Finally, evacuate, introduce inert atmosphere, heat the mixed solution to 290℃, and stir magnetically at a constant speed for 1.5h. After the reaction is completed, cool to room temperature, centrifuge with alcohol, and the purified NaYF4:1%Er 3+ The nanocrystals were dispersed in 8 mL of cyclohexane (the particle size of the nanocrystals was ∼32 nm, and the concentration of the nanocrystal dispersion was 0.05 mol / L).
[0070] (2) Preparation of glass fiber microsphere cavity: Strip a small section of the coating of commercial quartz optical fiber, clamp one end of the optical fiber with a vertical clamp, hang a weight on the other end, heat the middle of the stripped optical fiber with oxyhydrogen flame or CO2 laser, and use the gravity of the weight to pull the optical fiber into a micro / nano-scale tapered optical fiber. Then cut the tapered optical fiber from the middle, focus the oxyhydrogen flame or CO2 laser on the tail end of the single-taper optical fiber, melt the end, and automatically form a microsphere cavity (diameter 8μm) under the action of surface tension.
[0071] (3) Immerse the glass fiber microsphere cavity obtained in step (2) into the NaYF4:1%Er obtained in step (1) 3+ Nanocrystals were dispersed in cyclohexane for 1 min and then reacted with NaYF4:1%Er 3+ The nanocrystals are uniformly coated on the surface of the microsphere cavity.
[0072] (4) The optical fiber microsphere cavity coated with nanocrystals is placed in a muffle furnace, and the temperature is increased to 250°C at a heating rate of 5°C / min, and then kept at this temperature for 3 hours. After the end of the heat preservation, it is cooled to room temperature in the furnace.
[0073] (5) Using a fiber fusion splicer, the heat-treated tail fiber of the microsphere cavity is fused with the beam combining end of the fiber beam splitter. One end of the beam splitter is fused with a 980nm fiber laser, and the other end is connected to a fiber spectrometer. When connecting, a filter is placed between the fiber and the spectrometer to obtain a NaYF4:1%Er 3+ A miniature all-fiber pH sensor with nanocrystal-coated quartz fiber microsphere cavity.
[0074] The NaYF4:1%Er 3+ The schematic diagram of the structure of the nanocrystalline micro all-fiber pH sensor is similar to that of Example 1 and will not be described in detail.
[0075] The spectrum of the miniature all-fiber pH sensor obtained in this embodiment is shown in Fig.10 As shown in the figure, it can be observed from the fluorescence photograph that the size of the microspheres can reach 8 μm. Therefore, the spatial resolution of the miniature all-fiber pH sensor obtained in this embodiment can reach the micron level. 3+ The emission intensity ratio of green light and red light will show regular changes at different pH values. By utilizing this rule, the miniature all-optical fiber pH sensor obtained in this embodiment can monitor pH values in different environments.
[0076] Example 3
[0077] Based on NaYF4:40%Yb 3+ ,1%Tm 3+The invention discloses a micro all-fiber pH sensor of NaYF4 nanoparticles and a preparation method thereof, comprising the following steps:
[0078] (1)NaYF4:40%Yb 3+ ,1%Tm 3+ @ Preparation of NaYF4 nanoparticles:
[0079] Add 3mL of oleic acid and 7mL of 1-octadecene to a 50mL two-necked flask, add 2mL of 0.2mol / L Ln(CH3CO2)3 (Ln=Y, Yb and Tm) solution according to the established stoichiometric ratio (Y:Yb:Tm=59:40:1), stir magnetically at 150℃ for 1h, and cool to room temperature. Then dissolve 1mmol of NaOH and 1.6mmol of NH4F in 5mL of methanol solution, add to the above mixed solution, stir magnetically at 50℃ for 0.5h, then heat to 100℃ and stir for 1h. Finally, evacuate, introduce inert atmosphere, heat the mixed solution to 290℃, and stir magnetically at 1.5h. After the reaction is completed, cool to room temperature, centrifuge with alcohol, and use the purified NaYF4:40%Yb 3+ ,1%Tm 3+ The nanocrystals were dispersed in 4 mL of cyclohexane (the particle size of the nanocrystals was ∼40 nm, and the concentration of the nanocrystal dispersion was 0.1 mol / L).
[0080] The NaYF4:40%Yb 3+ ,1%Tm 3+ Nanocrystals were used as crystal nuclei, and a layer of NaYF4 was grown on their surface using a similar method to prepare NaYF4:40% Yb 3+ ,1%Tm 3+ @NaYF4 core-shell structure nanoparticles. Add 3mL oleic acid, 7mL 1-octadecene and 2mL 0.2mol / L Y(CH3CO2)3 solution into a 50mL two-necked flask. Stir the mixed solution at 150℃ for 1h and cool to room temperature. Then add 4mL NaYF4:20%Yb obtained in the previous step. 3+ ,1%Tm 3+ Then, 1 mmol of NaOH and 1.6 mmol of NH4F were dissolved in 5 mL of methanol solution and added to the above mixed solution. The mixture was stirred at 50 °C for 0.5 h and then heated to 100 °C for 1 h. Finally, the mixture was vacuumed and inert atmosphere was introduced. The mixture was heated to 290 °C and stirred at a constant speed for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature and purified by centrifugation with alcohol. The purified NaYF4:40%Yb 3+ ,1%Tm 3+@NaYF4 nanoparticles were dispersed in 4 mL of cyclohexane (the particle size of the nanoparticles was ~55 nm, and the concentration of the nanoparticle dispersion was 0.1 mol / L in terms of nanocrystals).
[0081] (2) Preparation of glass fiber microsphere cavity: Strip a small section of the coating of commercial quartz optical fiber, clamp one end of the optical fiber with a vertical clamp, hang a weight on the other end, heat the middle of the stripped optical fiber with oxyhydrogen flame or CO2 laser, and use the gravity of the weight to pull the optical fiber into a micro / nano-scale tapered optical fiber. Then cut the tapered optical fiber from the middle, focus the oxyhydrogen flame or CO2 laser on the tail end of the single-taper optical fiber, melt the end, and automatically form a microsphere cavity (diameter 105μm) under the action of surface tension.
[0082] (3) Immerse the glass fiber microsphere cavity obtained in step (2) into the NaYF4:40% Yb 3+ ,1%Tm 3+ @NaYF4 nanoparticles were placed in a cyclohexane dispersion for 30 seconds. Through van der Waals interaction, NaYF4:40% Yb 3+ ,1%Tm 3+ @NaYF4 nanoparticles are uniformly coated on the surface of the microsphere cavity.
[0083] (4) The optical fiber microsphere cavity coated with nanoparticles was placed in a muffle furnace, and the temperature was increased to 250°C at a heating rate of 5°C / min, and then kept at this temperature for 3 hours. After the end of the heat preservation, it was cooled to room temperature in the furnace.
[0084] (5) Using a fiber fusion splicer, the heat-treated tail fiber of the microsphere cavity is fused with the beam combining end of the fiber beam splitter. One end of the beam splitter is fused with a 980nm fiber laser, and the other end is connected to a fiber spectrometer. When connecting, a filter is placed between the fiber and the spectrometer to obtain a NaYF4:40% Yb 3+ ,1%Tm 3+ @A miniature all-fiber pH sensor with NaYF4 nanoparticles encapsulating a quartz fiber microsphere cavity.
[0085] The NaYF4:40% Yb 3+ ,1%Tm 3+ @The schematic diagram of the structural device of the miniature all-fiber pH sensor of NaYF4 nanoparticles is similar to that in Example 1 and will not be repeated here.
[0086] The spectrum of the miniature all-fiber pH sensor obtained in this embodiment is as follows: Fig.11 As shown, a clear Tm 3+From the fluorescence photograph in the figure, it can be observed that the size of the microspheres can reach more than 100 μm. Therefore, in combination with Example 2, the size of the microspheres can be adjusted, that is, the spatial resolution of the pH value detection can be adjusted. Similar to Example 1, Tm 3+ The emission intensity ratio of blue light and red light will show regular changes with the change of pH value. By utilizing this law, the miniature all-optical fiber pH sensor obtained in this embodiment can monitor pH value in different environments.
[0087] Example 4
[0088] Based on NaGdF4:20%Yb 3+ ,2%Er 3+ A nanocrystalline micro all-optical pH sensor and a preparation method thereof, comprising the following steps:
[0089] (1)NaGdF4:20%Yb 3+ ,2%Er 3+ Preparation of nanocrystals: Add 4mL of oleic acid and 6mL of 1-octadecene to a 50mL two-necked flask, add 2mL of 0.2mol / L Ln(CH3CO2)3 (Ln=Gd,Yb,Er) solution according to the established stoichiometric ratio (Gd:Yb:Er=79:20:1), stir magnetically at a constant speed for 1h at 150℃, and cool to room temperature. Then dissolve 1mmol of NaOH and 1.28mmol of NH4F in 4.2mL of methanol solution, add to the above mixed solution, stir magnetically at a constant speed for 0.5h at 50℃, then heat to 100℃ and stir for 1h. Finally, evacuate, introduce inert atmosphere, heat the mixed solution to 290℃, and stir magnetically at a constant speed for 1.5h. After the reaction is completed, cool to room temperature, centrifuge with alcohol, and use the purified NaGdF4:20%Yb 3+ ,2%Er 3+ The nanocrystals were dispersed in 40 mL of cyclohexane (the particle size of the nanocrystals was ∼11 nm, and the concentration of the nanocrystal dispersion was 0.01 mol / L).
[0090] (2) Preparation of glass fiber microsphere cavity: Strip a small section of the coating of commercial quartz optical fiber, clamp one end of the optical fiber with a vertical clamp, hang a weight on the other end, heat the middle of the stripped optical fiber with oxyhydrogen flame or CO2 laser, and use the gravity of the weight to pull the optical fiber into a micro / nano-scale tapered optical fiber. Then cut the tapered optical fiber from the middle, focus the oxyhydrogen flame or CO2 laser on the tail end of the single-taper optical fiber, melt the end, and automatically form a microsphere cavity (diameter 53μm) under the action of surface tension.
[0091] (3) Immerse the glass fiber microsphere cavity obtained in step (2) into the NaGdF4:20%Yb 3+,2%Er 3+ The nanocrystals were dispersed in cyclohexane for 2 min and NaGdF4:20%Yb 3+ ,2%Er 3+ The nanocrystals are uniformly coated on the surface of the microsphere cavity.
[0092] (4) The optical fiber microsphere cavity coated with nanocrystals is placed in a muffle furnace, and the temperature is increased to 250°C at a heating rate of 5°C / min, and then kept at this temperature for 3 hours. After the end of the heat preservation, it is cooled to room temperature in the furnace.
[0093] (5) Using a fiber fusion splicer, the heat-treated tail fiber of the microsphere cavity is fused with the beam combining end of the fiber beam splitter. One end of the beam splitter is fused with an 800 nm fiber laser, and the other end is connected to a fiber spectrometer. When connecting, a filter is placed between the fiber and the spectrometer to obtain a NaGdF4:20% Yb 3+ ,2%Er 3+ A miniature all-fiber pH sensor with nanocrystal-coated quartz fiber microsphere cavity.
[0094] The NaGdF4:20%Yb 3+ ,2%Er 3+ The schematic diagram of the structure of the nanocrystalline micro all-fiber pH sensor is similar to that of Example 1 and will not be described in detail.
[0095] The spectrum of the miniature all-fiber pH sensor obtained in this embodiment is as follows: Fig.12 As shown, similar to Example 1, Er 3+ The emission intensity ratio of green light and red light will show regular changes at different pH values. By utilizing this rule, the miniature all-optical fiber pH sensor obtained in this embodiment can monitor pH values in different environments.
[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other modifications, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals, characterized in that: The invention comprises rare earth ion doped nanoparticles, a glass fiber microsphere cavity and an optical fiber optical path. The rare earth ion doped nanoparticles are loaded on the surface of the glass fiber microsphere cavity. The glass fiber microsphere cavity and the optical fiber optical path are interconnected to form an optical path. The rare earth ion doped nanoparticles are rare earth ion doped nanocrystals or nanoparticles of a matrix wrapped around rare earth ion doped nanocrystals. The rare earth ion doped nanocrystals have a light response to pH. The optical fiber optical path provides excitation light and collects emission light.
2. The miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals according to claim 1, characterized in that: The rare earth ion-doped nanocrystal comprises rare earth ions and a matrix; The size of the rare earth ion doped nanoparticles is less than 100 nm.
3. The miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals according to claim 2, characterized in that: The rare earth ion is selected from Er 3+ 、Tm 3+ At least one of; The matrix is rare earth fluoride; Rare earth ion-doped nanocrystals also include Yb 3+ Co-doping.
4. The miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals according to claim 3 is characterized in that: The matrix is selected from a mixture of one or more of NaYF4, NaGdF4, NaLuF4, NaScF4, NaYbF4 and LiYF4.
5. The miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals according to claim 1, characterized in that: The diameter of the glass fiber microsphere cavity is 8 μm to 300 μm; The optical fiber optical path is connected to the excitation source and the spectrometer through a fiber optic beam splitter.
6. The method for preparing a miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals according to claims 1 to 5, characterized in that: The following steps are involved: (1) dispersing rare earth ion-doped nanoparticles in a non-polar organic solvent to obtain a dispersion; (2) immersing the glass fiber microsphere cavity in the dispersion solution and allowing it to stand, taking it out for heat treatment, and cooling it to obtain a glass fiber microsphere cavity loaded with rare earth ion-doped nanoparticles; (3) Connecting the glass fiber microsphere cavity loaded with rare earth ion-doped nanoparticles to the optical fiber optical path to obtain a miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals.
7. The preparation method according to claim 6, characterized in that: In step (1), the rare earth ion-doped nanoparticles are prepared by a wet chemical method; In step (1), the non-polar organic solvent is cyclohexane; In step (1), the concentration of the rare earth ion-doped nanoparticles in the dispersion is 0.005 mol / L to 0.1 mol / L based on the rare earth ion-doped nanocrystals.
8. The preparation method according to claim 6, characterized in that: In step (2), the standing time is 10s to 5min; In step (2), the heat treatment temperature is 250 to 300° C., and the heat treatment time is 2 to 5 hours; In step (2), the preparation method of the glass optical fiber microsphere cavity is as follows: The glass optical fiber is heated, and the glass optical fiber is drawn into a tapered optical fiber by a melt drawing method, and is cut from the thinnest part to obtain a single-taper glass optical fiber. The tapered end of the single-taper glass optical fiber is heated and melted, and under the action of surface tension, the melted tapered end automatically forms a micro-spherical cavity; In step (3), the cavity of the glass fiber microsphere loaded with rare earth ion-doped nanoparticles is connected to the optical fiber optical path by fusion connection between the optical fiber end of the glass fiber microsphere and the optical fiber of the optical fiber optical path.
9. The preparation method according to claim 8, characterized in that: Glass optical fiber is quartz optical fiber.
10. Application of the miniature all-fiber pH sensor based on rare earth ion-doped nanocrystals as claimed in any one of claims 1 to 5 in monitoring pH value.
Citation Information
Patent Citations
pH nanometer sensing material with upconversion luminescence property, and preparation method thereof
CN103468260A
Highly-doped broadband excited rare earth up-conversion fluorescent nanomaterial and preparation method thereof
CN103788952A
Highly-doped multi-band excitation rare earth upconversion fluorescence nano material and preparation method thereof
CN105419801A
Preparation method and application method of core-shell nanocrystal cell temperature sensor
CN108192592A
Multistage anti-counterfeiting material with three-primary-color orthogonal up-conversion fluorescence characteristic and application of multistage anti-counterfeiting material
CN111681532A
Cited By
Optical fiber micro-flow cavity MZI interference type pH sensor and preparation method thereof
CN122130603A